2015
DOI: 10.1016/j.amepre.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and the Developing Human

Abstract: The elimination of cigarettes and other combusted tobacco products in the U.S. would prevent tens of millions of tobacco-related deaths. It has been suggested that the introduction of less harmful nicotine delivery devices, such as electronic cigarettes or other electronic nicotine delivery systems, will accelerate progress toward ending combustible cigarette use. However, careful consideration of the potential adverse health effects from nicotine itself is often absent from public health debates. Human and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
138
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(144 citation statements)
references
References 73 publications
(62 reference statements)
3
138
0
3
Order By: Relevance
“…On the one hand, the low and zero prevalence of e-cigarette use among former and never-smokers is encouraging. On the other hand, the fact that nearly one third of current tobacco cigarette smokers also use e-cigarettes, a product for which nicotine levels and nicotine-related impurities have been shown to vary across brands (England et al, 2015), may be of concern if it results in a greater level of nicotine exposure during pregnancy. Alternatively, if e-cigarette use among pregnant smokers signals interest in smoking cessation, this could be leveraged to reduce the risk of nicotine exposure in this group (Chivers et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the low and zero prevalence of e-cigarette use among former and never-smokers is encouraging. On the other hand, the fact that nearly one third of current tobacco cigarette smokers also use e-cigarettes, a product for which nicotine levels and nicotine-related impurities have been shown to vary across brands (England et al, 2015), may be of concern if it results in a greater level of nicotine exposure during pregnancy. Alternatively, if e-cigarette use among pregnant smokers signals interest in smoking cessation, this could be leveraged to reduce the risk of nicotine exposure in this group (Chivers et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although many have concluded that e-cigarettes are likely less harmful than conventional cigarettes, 36 there is, however, evidence suggesting they are not harmless. 37 For example, although the level of nicotine delivered to users via an e-cigarette is variable and the threshold for addiction to nicotine associated with e-cigarette use in youth is unknown, nicotine itself is still considered a highly addictive substance. In a neuroimaging study, exposure to intravenous nicotine increased neuronal activity in brain regions also shown to produce reinforcing and dependence properties associated with cocaine, amphetamine and opiates.…”
Section: Discussionmentioning
confidence: 99%
“…Use of nicotine in vaporizers can harm the developing adolescent brain (Breland et al, 2016), particularly affecting attention and learning. Nicotine also has a high potential for addiction (England et al, 2015; Kandel and Kandel, 2015). Recent studies show that adolescent use of e-cigarettes is associated with intention to use and actual use of regular cigarettes (Bunnell et al, 2015; Dutra and Glantz, 2014; Leventhal et al, 2015) and with progression to regular cigarette smoking (Primack et al, 2015), although additional research is needed.…”
Section: Introductionmentioning
confidence: 99%